Dissecting LuxS/AI-2 quorum sensing system-mediated phenyllactic acid production mechanisms of Lactiplantibacillus plantarum L3. (April 2023) - Chai, Yunmei; Ma, Qingwen; Nong, Xin; Mu, Xinyue; Huang, Aixiang
Graphical abstract: Highlights: The synthesis of PLA in L. plantarum L3 was regulated by LuxS/AI-2 QS. 1291 differentially expressed proteins were identified in the synthesis of PLA. LuxS, araT, and ldh are key proteins affecting the synthesis of PLA in L. plantarum L3. The central pathway in L. plantarum L3 is the PLA synthesis from phenylalanine. Abstract: The phenyllactic acid (PLA) produced by lactic acid bacteria (LAB) inhibits fungi and facilitates the quality control of fermented milk. A strain of Lactiplantibacillus plantarum L3 ( L. plantarum L3) with high PLA production was screened in the pre-laboratory, but the mechanism of its PLA formation is unclear. The amount of autoinducer-2 (AI-2) increased with increasing culture time, as did cell density and PLA. The results in this study suggest that PLA production in L. plantarum L3 may be regulated by the LuxS/AI-2 Quorum Sensing (QS) system. Tandem mass tag (TMT) quantitative proteomics analysis showed that a total of 1291 differentially expressed proteins (DEPs) were quantified in the incubated for 24 h compared with the incubated for 2 h, of which 516 DEPs were up-regulated and 775 DEPs were down-regulated. Among them, S-ribosomal homocysteine lyase ( luxS ), aminotransferase ( araT ), and lactate dehydrogenase ( ldh ) are the key proteins for PLA formation. The DEPs were mainly involved in the QS pathway and the core pathway of PLA synthesis. Furanone effectively inhibited the production of L. plantarum L3 PLA. In addition, Western blot analysis demonstrated that luxS, araT, and ldh were the key proteins regulating PLA production. This study reveals the regulatory mechanism of PLA based on the LuxS/AI-2 QS system, which provides a theoretical basis for the efficient and large-scale production of PLA in industries in the future.